Pengaruh Work Engagement terhadap Work-Family Enrichment pada Perawat Gigi - Ranti Nurbayanti; Dinda Dwarawati (UNISBA Press, 2023)
Abstract. Work-Family Enrichment is defined as the extent to which the experience of one role is able to improve the quality of life of other roles (Greenhaus & Powel, 2006). Work engagement is a positive motivational affective state characterized by vigor, dedication, and absorption (Schaufeli et al., 2002), and is influenced by job demands and job resources (Schaufeli & Bakker, 2004). The purpose of this study was to determine the effect of Work Engagement on Work-Family Enrichment in dental nurses. With reference to Work-Family Enrichment theory from Greenhaus & Powell (2006) and Work Engagement theory from Schaufeli & Bakker (2002). This study used a causal quantitative research method with a sample of 71 dental nurses. The data analysis technique used multiple linear regression test. To measure Work Engagement using the Utrecht Work Engagement Scale-9 (UWES-9) developed by Schaufelli & Bakker (2003). Meanwhile, to measure Work-Family Enrichment using a measurement scale from Carlson et al., (2006). The results of the study show that the Rsquare (R2) value is 0.344, meaning that Work Engagement can have a 34.4% effect on Work-Family Enrichment. With dimensions of vigor to WFE of 33.4% and dimensions of vigor to FWE of 28.4% as the dimensions that contribute the greatest influence. Abstrak. Work-Family Enrichment dimaknai sebagai sejauh mana pengalaman dari suatu peran mampu meningkatkan kualitas kehidupan peran lainnya (Greenhaus & Powel, 2006). Work engagement merupakan keadaan afektif motivasional positif yang ditandai dengan adanya vigor, dedication, dan absorption (Schaufeli et al., 2002), dan dipengaruhi oleh job demands dan job resources (Schaufeli & Bakker, 2004). Tujuan dari penelitian ini adalah untuk mengetahui pengaruh Work Engagement terhadap Work-Family Enrichment pada perawat gigi . Dengan mengacu pada teori Work-Family Enrichment dari Greenhaus & Powell (2006) dan teori Work Engagement dari Schaufeli & Bakker (2002). Penelitian ini menggunakan metode penelitian kuantitatif kausalitas dengan sampel sebanyak 71 orang perawat gigi. Teknik analisis data menggunakan uji regresi linier berganda. Untuk mengukur Work Engagement menggunakan Utrecht Work Engagement Scale-9 (UWES-9) yang dikembangkan oleh Schaufelli & Bakker (2003). Sedangkan untuk mengukur Work-Family Enrichment menggunakan skala pengukuran dari Carlson et al., (2006). Hasil penelitian menunjukkan nilai Rsquare (R2) sebesar 0.344, artinya Work Engagement dapat memberikan pengaruh sebesar 34,4% terhadap Work-Family Enrichment. Dengan dimensi vigor terhadap WFE sebesar 33,4% dan dimensi vigor terhadap FWE sebesar 28,4% sebagai dimensi yang memberikan sumbangan pengaruh terbesar.